(untitled) (Research, Society and Development, 2020)
The aim of the investigation was to synthesize 3 mol% yttria-stabilized zirconia (3Y-TZP) powders via polymeric precursor method (PPM). The precursor solution was preheated at 350ºC for 3h, subsequently thermally treated at 500ºC for 3h and 800ºC for 6h. The obtained materials were analyzed by Thermogravimetry-Derivative Thermogravimetry (TG/DTG), Differential Thermal Analysis (DTA), powder X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Two commercially available Y-TZP ceramic systems were chosen for comparison. XRD analysis of the synthesized 3Y-TZP powders revealed the crystallization of the tetragonal phase, while both commercial systems showed the coexistence of the monoclinic and tetragonal phases. SEM analysis showed that the powders thermally treated at 800°C consist of agglomerated spherical nanoparticles. Morphology of commercial systems also revealed nanosized spherical particles. Results revealed that the PPM led to ceramics with structural and morphological properties comparable to commercially available reinforced dental ceramics.